(untitled) (Journal of Nepal Physical Society, 2020)
The daily aerosol optical depth (AOD) data are derived from AERONET over Bode, Bhaktapur (27.68° N, 85.39° E, 1297 m above sea level) for a period of one year 2013. Annual mean of Atmospheric turbidity factors are calculated. The effect of different physical as well as meteorological parameters on the Linke turbidity factor was analyzed. The yearly mean of solar insolation, Angstrom exponential (α),Angstrom coefficient of turbidity (β) and Linke turbidity (LT) were found 4.70 ± 1.10kWh/m2/day, 1.13 ± 0.21 ,0.18 ± 0.14 and 5.70 ± 2.46 respectively. Annual average of visibility is 2.98 ± 2.13 km. Result of this research work is beneficial for the further identification, impact and analysis of atmospheric turbidity at different places.